2010
DOI: 10.2174/1874440001004010046
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Motion in Figurative Language Comprehension

Abstract: Abstract:In this visual world eye tracking study we explored simulation of fictive motion during language comprehension in figurative sentences in Hindi. Eye movement measures suggest that language comprehenders gaze longer at visual scenes on hearing fictive motion sentences compared to their literal counterparts. The results support previous findings in English and provide cross linguistic evidence for the simulation and embodied views of language processing. We discuss the findings in the light of neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Another possible explanation is that the left temporo-occipital effects are related to the different semantic processes in literal phrases and idioms, because the three conditions have different semantic features (e.g., semantic distance). Previous studies have shown that these temporo-occipital areas are also involved in semantic-conceptual processing (Ghosh et al, 2010;Hinojosa et al, 2000), and eye-tracking research has also found that more fixations and longer gaze duration at the visual scenes when hearing figurative sentences compared to their literal counterparts (Singh and Mishra, 2010).…”
Section: Role Of Other Cortical Regions and Task Demands In Idiom Promentioning
confidence: 97%
“…Another possible explanation is that the left temporo-occipital effects are related to the different semantic processes in literal phrases and idioms, because the three conditions have different semantic features (e.g., semantic distance). Previous studies have shown that these temporo-occipital areas are also involved in semantic-conceptual processing (Ghosh et al, 2010;Hinojosa et al, 2000), and eye-tracking research has also found that more fixations and longer gaze duration at the visual scenes when hearing figurative sentences compared to their literal counterparts (Singh and Mishra, 2010).…”
Section: Role Of Other Cortical Regions and Task Demands In Idiom Promentioning
confidence: 97%
“…This suggests that the mode of visual processing of a picture described by a fictive motion sentence is somehow different from the mode of visual processing of the same picture described by a nonfictive motion sentence. In a related study, Singh and Mishra [38] found that comprehenders gazed for a longer period of time at visual scenes when hearing metaphoric fictive motion sentences compared to literal sentences. This indicates that when a static image is metaphorically/fictively described in terms of a motion event, that motion is mentally simulated and realized in the patterns of eye movements.…”
Section: Eye-tracking Studiesmentioning
confidence: 94%
“…This suggests that the metaphoric conceptualization of some emotional states and emotional terms such as anger can be reflected in eye movements. Interestingly, some works have suggested that this can happen not only for emotion-related concepts but also for other categories of abstract concepts that are metaphorically described in terms of movement (e.g., Singh and Mishra, 2010).…”
Section: Document Co-citation Analysismentioning
confidence: 99%